(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Malaria remains a major public health problem in Nigeria. Information on clients’ knowledge and treatment seeking behaviour might improve or sustain the rational management of the disease and treatment outcome. Objectives: This study assessed the knowledge and treatment seeking behaviour for the disease among undergraduate students of two Faculties of the University of Jos. Materials and Method: The study employed a cross-sectional strategy in which a self-administered questionnaire was administered to two hundred and two (202) four hundred (400) and five hundred (500) levels Veterinary Medicine and Pharmaceutical sciences Faculty students of the University. The collected data was analyzed using IBM-SPSS® version 23 software. Results: The total possible maximum correct knowledge score of the respondents was 10, and there mean (± SD) knowledge score was 7.77 (± 1.27), with majority (59.9%) having good knowledge of malaria and its management. Most of them either had moderate (38.1%) or good (36.1%) treatment seeking behaviour for the disease. Some factors including religion, level of education, patronage of healthcare facilities, and knowledge of the disease and its management were significant predictors of students’ treatment seeking behaviour for malaria. Conclusion: Despite the fact that a high proportion of the students had good knowledge, their treatment seeking attitudes for the disease were not correspondingly high, implying the existence of a possible gap between the students’ theoretical knowledge on the disease and actual treatment seeking behaviour for the disease.